Measuring the Impact of High Order Harmonics on the Transformer No-Load Power Losses - Mihail Digalovski, Goga Cvetkovski, Krste Najdenkoski, Goran Rafajlovski (Faculty of Electrical Engineering and Information Technologies, Ss. Cyril and Methodius University in Skopje, North Macedonia, 2022)
Transformers are normally designed and built for use at rated frequency, sinusoidal voltages and load current. A non-sinusoidal sources and non-linear load on a transformer leads to harmonic power losses which cause increased operational costs and additional heating in certain transformer parts. It leads to higher losses, early fatigue of insulation, premature failure and reduction of the useful life of the transformer. In this work a dry type 500 VA three phase transformer is powered, once directly by to the grid and then through voltage inverter. The no-load losses and high order harmonics are measured using power analyzer. The power losses are also determined analytically obtained by deriving equations for the no-load power losses depending on the harmonics order, its frequency and the amplitude of the magnetic flux density, and compared with the measured ones.
Keywords: Power transformer, power losses, harmonic losses, no-load losses